Determination of the Optimal Load Setting for Arm Crank Anaerobic Testing in Men and Women - Forbes, S. C.; Kennedy, M. D.; Boule, N. B.; Bell, G. (International Journal of Sports Medicine, 2014)
This study compared different relative load factors for eliciting the highest peak 5 s and mean 30 s absolute power output (watts) during an arm crank 30 s Wingate anaerobic power test in 40 upper body trained and recreationally active men and women. The relative load factor of 0.075 kg · kg− 1 BM elicited a higher peak 5 s power output than 0.070 and 0.080 kg · kg− 1 for trained males, and 0.070 was higher than 0.055 and 0.080 kg · kg− 1 for active males (P<0.05). In trained women, the peak 5 s power output was greatest at 0.065 kg · kg− 1 and 0.060 kg · kg− 1 for active women. Mean 30 s power output at a relative load factor of 0.060, 0.065 and 0.070 kg · kg− 1 was higher than 0.080, 0.085 and 0.090 kg · kg− 1 in trained men, and mean power output at 0.080 kg · kg− 1 was lower than all other relative load factors in active men (P<0.05). Mean 30 s power was greatest at 0.050 kg · kg− 1 for trained and active women. In conclusion, the optimal relative load factor was different for eliciting peak 5 s and mean 30 s power outputs during an arm crank Wingate anaerobic test and depends on training status and gender.
Keywords: ergometry; power output; fatigue